Biotic and Abiotic factors in the distribution of resident fish species : a case study from two islets and an adjacent shoreline in Terceira Island, Azores, Portugal - Medeiros, João (2015)
With this poster we aim to disclose the ecological characteristics of the resident ichthyofauna in three distinct SE- NW aligned sites off the S coast of Terceira Island, Azores, Portugal. We collected both direct and indirect data about those species near the shoreline – Serretinha, in a close by islet complex – Cabras and over an offshore rocky outcrop – Fradinhos. [...].